Restabelecimento funcional do tendão extensor digital longo submetido a ressecção parcial em equinos: Observação macroscópica, histopatológica e ultra-sonográfica - Gianini, Carla Guimarães [UNESP]; Hussni, Carlos Alberto [UNESP]; Alves, Ana Liz Garcia [UNESP]; Nicoletti, José Luiz de Mello [UNESP]; Thomassian, Armen [UNESP]; Sequeira, Julio Lopes [UNESP]; Beier, Suzane Lilian [UNESP]; Weigel, Rebeca Alves [UNESP] (My University, 2006)
The objective of this work was to study the macroscopic, ultrasonographic and histopathologic aspects from the newly formed cicatricial tissue at the site of the partial resection of the long digital extensor tendon in 10 equines at the moment of functional restoration of the limb with the animal in walk locomotion. The macroscopic exam was performed every 48 hours, the planimetric mensuration every 10 days, the ultrasonographic exam every 15 days and the histopathologyc exam at the end of the study. The wounds showed granulation tissue in retraction, without total lesion epithelization, and the aspects ultrasonographics revealed wound healing with newly formed tissues with variable density and high neovascularization without tendon structural reorganization. The histopathology showed newly formed vascularized tissue, with leukocytic infiltrate and collagenous deposition without full epithelization. The cicatrization tissue formed in the resection region of the tendon, immature and without the structural organization of the normal tendon, showed to be able to functional restoration of the operated limb.
Functional restoration of the long digital extensor tendon in horses after parcial tenectomy: Gross, histopathologycal and ultrasonographic evaluation
Keywords: Equines; Healing; Long digital extensor tendon; Tendon rupture; Animalia; Equidae